Pengaruh Konsentrasi dan Waktu Aplikasi Giberelin terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo L.): Effect of Gibberellin Concentration and Application Timing on the Growth and Yield of Melon (Cucumis melo L.) - Oktaviana Fasya, Elfira Rizki; Hidayat, Ramdan; Nugrahani, Pangesti (Agrocentrum, 2025)
Melon (Cucumis melo L.) is a horticultural variety widely cultivated in Indonesia due to its sweet taste, nutritional content, and high economic value. This study aimed to determine the optimal concentration and application timing of gibberellin (GA₃) to enhance the growth and yield of Fujisawa melon plants. The research was arranged in a factorial design using a Completely Randomized Design (CRD) with two factors and four replications. The first factor was gibberellin concentration (0, 50, 100, and 150) ppm, and the second factor was application timing (pre-anthesis, anthesis, and post-anthesis stages). The results showed a significant interaction between gibberellin concentration and application timing on fruit volume. The single treatment of 100 ppm GA₃ had the best effect on plant height, harvest time, and number of fruits formed.